Composition with improved storage stability
By using a resin composition containing a reactive silicon-based polyoxyalkylene polymer, a surface-treated calcium carbonate and an epoxy compound in a high temperature and multi-humidity environment, the problem of poor storage stability of the curable resin composition is solved, and good storage stability and extended storage time are achieved.
Patent Information
- Application Number
- CN202110651742.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-12
- Filing Date
- 2021-06-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-06-11
AI Technical Summary
The prior art has problems of insufficient sealing properties and rising viscosity when storing curable resin compositions in high temperature and multi-humidity environments, resulting in poor storage stability.
The resin composition using a deposition-amounted curable resin composition contains a polyoxyalkylene polymer with a reactive silicon group, calcium carbonate and epoxy compounds after surface treatment with a fatty acid compound, and is stored in a high temperature and multi-humidity environment.
A decomposition-amounted curable resin composition with good storage stability in high temperature and humidity environment is realized, which avoids viscosity increase and gelation and extends storage time.
Smart Images

Figure BDA0003111761380000221 
Figure BDA0003111761380000281 
Figure BDA0003111761380000311
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition for a pre-packaged curable resin composition. Background Art
[0002] It is known that "polyoxyalkylene polymers having reactive silicon groups" have the following properties: cross-linking occurs at room temperature through the formation of siloxane bonds accompanied by a hydrolysis reaction of the reactive silicon groups caused by moisture, etc., thereby obtaining a rubber-like cured product. Polyoxyalkylene polymers having reactive silicon groups are already industrially produced and widely used as raw material resins for applications such as sealing materials, adhesives, and coatings.
[0003] The physical properties of the cured product can be improved by adding a filler including a reactive plasticizer and surface-treated calcium carbonate to a polyoxyalkylene polymer having a reactive silicon group (Patent Document 1).
[0004] Two-component curable resin compositions are separated into two components, a main agent and a curing agent, immediately before use. Therefore, they have the advantage of being able to maintain storage stability for about half a year to a year, and are particularly widely used in sealing materials for construction.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2011-94134 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, with respect to the prior art, there is room for further improvement from the perspective of storage stability, such as when the airtightness of the container sealed with the main agent (resin composition excluding the curing agent) is insufficient and / or when stored in a high temperature and high humidity environment, the viscosity of the main agent increases and the main agent gels.
[0010] One embodiment of the present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a resin composition for a pre-packaged curable resin composition having excellent storage stability even in a high-temperature and high-humidity environment.
[0011] Solution to the problem
[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention.
[0013] That is, one embodiment of the present invention includes the following configurations.
[0014] [1] A resin composition for a pre-packaged curable resin composition, comprising:
[0015] 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group,
[0016] 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and
[0017] Epoxy compound (C) 2 to 70 parts by weight,
[0018] In 100 mol % of the fatty acid compounds, the fatty acid compounds contain 12 mol % or less of fatty acid compounds having a hydrocarbon component with 14 or less carbon atoms.
[0019] [2] The resin composition for a pre-packaged curable resin composition according to [1], wherein the calcium carbonate (B) surface-treated with the fatty acid compound contains colloidal calcium carbonate surface-treated with a fatty acid compound.
[0020] [3] The resin composition for a packaged curable resin composition according to [1] or [2], further comprising 0.5 to 10.0 parts by weight of a photocurable substance (D).
[0021] [4] The resin composition for a pre-packaged curable resin composition according to any one of [1] to [3], further comprising 1.00 to 20.00 parts by weight of a hollow filler (E).
[0022] [5] The resin composition for a pre-packaged curable resin composition according to [4], wherein the hollow filler (E) contains hollow glass spheres.
[0023] [6] The resin composition for a pre-packaged curable resin composition according to any one of [1] to [5], further comprising a phthalate compound (F).
[0024] [7] A resin composition for a pre-packaged curable resin composition according to any one of [1] to [6], wherein the elongation at break of a cured product formed by curing the curable resin composition obtained by mixing the resin composition for a pre-packaged curable resin composition with a curing agent is 300% or more.
[0025] [8] A pre-packaged curable resin composition comprising the resin composition for a pre-packaged curable resin composition according to any one of [1] to [7].
[0026] [9] A method for producing a resin composition for a pre-packaged curable resin composition, the method comprising the step of mixing the following components (A) to (C):
[0027] 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group,
[0028] 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and
[0029] Epoxy compound (C) 2 to 70 parts by weight,
[0030] In 100 mol % of the fatty acid compounds, the fatty acid compounds contain 12 mol % or less of fatty acid compounds having a hydrocarbon component with 14 or less carbon atoms.
[0031] Effects of the Invention
[0032] According to one embodiment of the present invention, there is provided an effect of providing a resin composition for a pre-packaged curable resin composition having excellent storage stability even in a high-temperature and high-humidity environment. DETAILED DESCRIPTION
[0033] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various configurations described below, and various changes can be made within the scope indicated in the claims. In addition, embodiments or embodiments obtained by appropriately combining the technical means respectively disclosed in different embodiments or examples are also included in the technical scope of the present invention. In addition, by combining the technical means respectively disclosed in each embodiment, new technical features can also be formed. It should be noted that all academic literature and patent literature recorded in this specification are cited as references in this specification. In addition, in this specification, unless otherwise specified, "A to B" indicating a numerical range means "above A (including A and greater than A) and below B (including B and less than B)".
[0034] [Resin composition for pre-packaged curable resin composition]
[0035] The resin composition for the dispensing type curable resin composition according to one embodiment of the present invention contains: 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group, 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and 2 to 70 parts by weight of an epoxy compound (C), wherein in 100 mol % of the fatty acid compound, the fatty acid compound contains less than 12 mol % of fatty acid compounds having a hydrocarbon component with a carbon number of less than 14.
[0036] In the present specification, the “prepared curable resin composition” may be referred to as the “curable resin composition”, the “resin composition for the preparative curable resin composition” may be referred to as the “resin composition”, the “resin composition for the preparative curable resin composition according to one embodiment of the present invention” may be referred to as the “present resin composition”, the “polyoxyalkylene polymer (A) having a reactive silicon group” may be referred to as the “polyoxyalkylene polymer (A)”, and the “calcium carbonate (B) surface-treated with a fatty acid compound” may be referred to as the “surface-treated calcium carbonate (B)”.
[0037] Since the present resin composition has the above-mentioned structure, it has the advantage of being able to provide a pre-packaged curable resin composition having good storage stability even in a high-temperature and high-humidity environment. In other words, the present resin composition can be preferably used as a main component of a pre-packaged curable resin composition.
[0038] [Polyoxyalkylene polymer (A)]
[0039] The polyoxyalkylene polymer (A) contains a hydrolyzable (crosslinkable) silyl group (i.e., a reactive silicon group) such as an alkoxy group, a halogen atom, an acyloxy group, an alkenyloxy group, an amide group, or an oxime group bonded to a Si group at the end of the molecular chain, and has a repeating unit of oxyalkylene as a skeleton.
[0040] Specific examples of reactive silicon groups include trimethoxysilyl, triethoxysilyl, tri(2-propyleneoxy)silyl, triacetoxysilyl, dimethoxymethylsilyl, diethoxymethylsilyl, dimethoxyethylsilyl, (chloromethyl)dimethoxysilyl, (chloromethyl)diethoxysilyl, (methoxymethyl)dimethoxysilyl, (methoxymethyl)diethoxysilyl, (N,N-diethylaminomethyl)dimethoxysilyl, and (N,N-diethylaminomethyl)diethoxysilyl, but are not limited thereto. Among them, methyldimethoxysilyl, trimethoxysilyl, triethoxysilyl, (chloromethyl)dimethoxysilyl, (methoxymethyl)dimethoxysilyl, and (methoxymethyl)diethoxysilyl are preferred because they show high activity and can obtain a cured product with good mechanical properties. From the viewpoint of activity, trimethoxysilyl, (chloromethyl) dimethoxysilyl, and (methoxymethyl) dimethoxysilyl are particularly preferred. From the viewpoint of stability, methyl dimethoxysilyl, methyl diethoxysilyl, and triethoxysilyl are particularly preferred. From the viewpoint of safety, methyl diethoxysilyl and triethoxysilyl are particularly preferred. Since they are easy to manufacture, trimethoxysilyl, triethoxysilyl, and dimethoxymethylsilyl are particularly preferred.
[0041] The polyoxyalkylene polymer (A) preferably has 1.2 to 5.0 reactive silicon groups per molecule, more preferably 1.2 to 4.0 reactive silicon groups, and further preferably 1.2 to 3.0 reactive silicon groups. In the case where the polyoxyalkylene polymer (A) has 1.2 or more reactive silicon groups per molecule, the resin composition can provide a curable resin composition with good curability. Therefore, for the cured product that can be provided by the curable resin composition, good rubber elasticity can be obtained, and the recovery, durability and / or creep resistance of the cured product become good. The reactive silicon group can be located at the main chain end or the side chain end of the polyoxyalkylene polymer (A), or can also be located at both the main chain end and the side chain end. In particular, when only the main chain end of the polyoxyalkylene polymer (A) has a reactive silicon group, the effective mesh length in the cured product finally formed increases, so it is easy to obtain a rubber-like cured product with high strength and high elongation and low elastic modulus, so it is preferred.
[0042] The method for introducing the reactive silicon group into the polyoxyalkylene polymer can be carried out according to a known method. For example, the following methods I to III can be mentioned.
[0043] Method I: An organic polymer having a functional group such as a hydroxyl group is reacted with a compound having an active group and an unsaturated group that are reactive with the functional group to obtain an organic polymer having an unsaturated group. Next, the obtained organic polymer having an unsaturated group is reacted with a hydrosilane compound having a reactive silicon group by hydrosilylation.
[0044] Examples of the compound having a reactive active group and an unsaturated group used in Method I include allyl chloride, methallyl chloride, and unsaturated group-containing epoxy compounds such as allyl glycidyl ether.
[0045] Examples of the hydrosilane compound used in method I include halogenated silanes, alkoxysilanes, acyloxysilanes, and ketoxymate silanes, but are not limited thereto.
[0046] Examples of the halogenated silanes include trichlorosilane, methyldichlorosilane, dimethylchlorosilane, and phenyldichlorosilane.
[0047] Examples of the alkoxysilanes include trimethoxysilane, triethoxysilane, triisopropoxysilane, 1-[2-(trimethoxysilyl)ethyl]-1,1,3,3-tetramethyldisiloxane, diethoxymethylsilane, dimethoxymethylsilane, and phenyldimethoxysilane.
[0048] Examples of the acyloxysilanes include methyldiacetoxysilane and phenyldiacetoxysilane.
[0049] Examples of the ketoximate silanes include bis(dimethylketoximate)methylsilane and bis(cyclohexylketoximate)methylsilane.
[0050] Among these hydrosilane compounds, trialkoxysilanes are preferred from the viewpoint of hydrolyzability and mildness of reaction, and trimethoxysilane and triethoxysilane are more preferred.
[0051] It should be noted that, in order to obtain a polyoxyalkylene polymer (A) having a trimethoxysilyl group, it is preferred to use triethoxysilane as a raw material to synthesize a polymer having a triethoxysilyl group by the method described in WO2007-040143 and Japanese Patent Application Laid-Open No. 2008-285585, and then convert the triethoxysilyl group into a trimethoxysilyl group by using methanol. This is because trimethoxysilane is a very unstable compound, so it sometimes undergoes a disproportionation reaction to generate a low-boiling and self-igniting monosilane. In addition, trimethoxysilane is extremely dangerous to the human body, especially the eyes, and is therefore difficult to handle and difficult to obtain.
[0052] Method II: Examples include a method in which a compound having a mercapto group and a reactive silicon group is introduced into the unsaturated group site of an organic polymer having an unsaturated group obtained in the same manner as method I by a radical addition reaction in the presence of a radical initiator and / or a radical generating source.
[0053] Examples of the compound having a mercapto group and a reactive silicon group used in method II include, but are not limited to, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, mercaptomethyltrimethoxysilane, and mercaptomethyltriethoxysilane.
[0054] Method III: An organic polymer having a functional group such as a hydroxyl group, an epoxy group or an isocyanate group in the molecule is reacted with a compound having a functional group reactive with the functional group and a reactive silicon group.
[0055] In method III, examples of a method for reacting an organic polymer having a hydroxyl group with a compound having an isocyanate group and a reactive silicon group reactive with the hydroxyl group include, but are not limited to, the method disclosed in Japanese Patent Application Laid-Open No. 3-47825.
[0056] Examples of the compound having an isocyanate group and a reactive silicon group used in method III include, but are not limited to, γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, isocyanatemethyltrimethoxysilane, isocyanatemethyltriethoxysilane, and isocyanatemethyldimethoxymethylsilane.
[0057] When γ-mercaptopropyltrimethoxysilane and γ-isocyanatepropyltrimethoxysilane are used, the disproportionation reaction does not proceed as when trimethoxysilane is used. Therefore, the method using method II or method III is more preferable than the method using trimethoxysilane in method I.
[0058] On the other hand, a compound having a reactive silicon group (hereinafter also referred to as a silane compound) represented by the following general formula (1) does not undergo a disproportionation reaction:
[0059] H-(SiR 2 2O) m S i 2 2-R 3 -SiX3···(1)
[0060] (wherein, X each independently represents a hydroxyl group or a hydrolyzable group. 2m+2 R 2 R each independently represents a hydrocarbon group. 3 represents a divalent organic group. m represents an integer of 0 to 19).
[0061] Therefore, when introducing a group in which three hydrolyzable groups are bonded to one silicon atom in method I, it is preferred to use a silane compound represented by the general formula (1). 2 Each of R is independently a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrocarbon group having 1 to 8 carbon atoms, and still more preferably a hydrocarbon group having 1 to 4 carbon atoms. 3 It is preferably a divalent hydrocarbon group having 1 to 12 carbon atoms, more preferably a divalent hydrocarbon group having 2 to 8 carbon atoms, and still more preferably a divalent hydrocarbon group having 2 carbon atoms. m is most preferably 1.
[0062] Examples of the silane compound represented by the general formula (1) include 1-[2-(trimethoxysilyl)ethyl]-1,1,3,3-tetramethyldisiloxane, 1-[2-(trimethoxysilyl)propyl]-1,1,3,3-tetramethyldisiloxane, and 1-[2-(trimethoxysilyl)hexyl]-1,1,3,3-tetramethyldisiloxane.
[0063] The method of reacting an organic polymer having a hydroxyl group at the end with a compound having an isocyanate group and a reactive silicon group in the above-mentioned method I or method III can obtain a high conversion rate in a shorter reaction time, so it is preferred. On the other hand, the organic polymer having a reactive silicon group obtained by method I has a lower viscosity than the organic polymer having a reactive silicon group obtained by method III, and a curable resin composition with good operability can be obtained. In addition, for the organic polymer having a reactive silicon group obtained by method II, the odor derived from mercaptosilane is sometimes strong. Therefore, method I is particularly preferred.
[0064] In one embodiment of the present invention, the repeating units contained in the polyoxyalkylene polymer that becomes the main skeleton of the polyoxyalkylene polymer (A) include: polyoxyethylene units, polyoxypropylene units and polyoxybutylene units, etc., preferably polyoxypropylene units. In one embodiment of the present invention, the repeating units contained in the polyoxyalkylene polymer only need to have a crosslinkable silyl group in the molecule, but are not limited to this. For example, the repeating units (a) contained in the polyoxyalkylene polymer can be one or more selected from polyoxyethylene units, polyoxypropylene units and polyoxybutylene units, and (b) can also include one or more polyoxyalkylene units other than the above group.
[0065] Examples of methods for synthesizing polyoxyalkylene polymers include: (a) a polymerization method using a base catalyst such as KOH, (b) a polymerization method using a transition metal compound-porphyrin complex catalyst such as a complex obtained by reacting an organic aluminum compound with porphyrin as disclosed in Japanese Unexamined Patent Application Publication No. 61-215623, (c) Japanese Patent Publication No. 46-27250, Japanese Patent Publication No. 59-15336, U.S. Pat. No. 3278457, U.S. Pat. No. 3278458, U.S. Pat. No. 3278459, and U.S. Pat. No. 3278457. The present invention also includes, but is not limited to, a polymerization method using a composite metal cyanide complex catalyst (e.g., a zinc hexacyanocobaltate complex catalyst) as disclosed in US Pat. No. 459, US Pat. No. 3427256, US Pat. No. 3427334, US Pat. No. 3427335, etc., (d) a polymerization method using a catalyst comprising a polyphosphazene salt as disclosed in Japanese Patent Application Laid-Open No. 10-273512, (e) a polymerization method using a catalyst comprising a phosphazene compound as disclosed in Japanese Patent Application Laid-Open No. 11-060722, etc. Among these synthesis methods, a polymerization method in which an alkylene oxide is reacted with an initiator in the presence of a composite metal cyanide complex catalyst is preferred because it can obtain a polymer having a narrow molecular weight distribution.
[0066] Examples of the composite metal cyanide complex catalyst include Zn3[Co(CN)6]2 (zinc hexacyanocobaltate complex), etc. In addition, a catalyst in which an alcohol and / or an ether is coordinated to a zinc hexacyanocobaltate complex as an organic ligand may also be used.
[0067] The initiator is preferably a "compound having at least two active hydrogen groups" (hereinafter also referred to as "active hydrogen-containing compound"). Examples of the active hydrogen-containing compound include polyols such as ethylene glycol, diethylene glycol, propylene glycol, and glycerol, and linear and / or branched polyether compounds having a number average molecular weight of 500 to 20,000.
[0068] Examples of the alkylene oxide include ethylene oxide, propylene oxide, and isobutylene oxide.
[0069] The polyoxyalkylene polymer (A) in one embodiment of the present invention may be any of linear or branched. The number average molecular weight (Mn) of the polyoxyalkylene polymer (A) is a value measured by gel permeation chromatography (GPC) (polystyrene conversion), preferably 1,000 to 100,000, more preferably 2,000 to 50,000, and particularly preferably 3,000 to 35,000. For the above number average molecular weight, (a) when it is less than 1,000, there is a tendency for the elongation of the cured product to be insufficient, and (b) when it exceeds 100,000, the curable resin composition becomes high viscosity, so there is a tendency to be unfavorable in terms of operability. The molecular weight distribution (Mw / Mn) of the polyoxyalkylene polymer (A) measured by GPC is preferably 2.0 or less, more preferably 1.5 or less, and further preferably 1.4 or less.
[0070] As the polyoxyalkylene polymer (A), commercially available products may be used. For example, (a) Kaneka MS POLYMER and Kaneka CYRIL manufactured by Kaneka Co., Ltd., (b) EXCESTAR manufactured by AGC, (c) GENIOSIL manufactured by Wacker, etc. have been manufactured and sold for industrial use and can be easily obtained and used as the polyoxyalkylene polymer (A).
[0071] [Surface treated calcium carbonate (B)]
[0072] There is no particular restriction on the calcium carbonate forming the surface-treated calcium carbonate (B), for example, it can be any calcium carbonate in the heavy calcium carbonate obtained by (a) introducing CO2 gas into the water slurry of Ca(OH)2 and (b) mechanically crushing and classifying limestone. From the viewpoint of easily obtaining finer particles, the calcium carbonate forming the surface-treated calcium carbonate (B) is preferably colloidal calcium carbonate. In other words, the calcium carbonate (B) after surface treatment with a fatty acid compound preferably contains the colloidal calcium carbonate after surface treatment with a fatty acid compound, and more preferably the colloidal calcium carbonate after surface treatment with a fatty acid compound.
[0073] The BET specific surface area of calcium carbonate forming the surface-treated calcium carbonate (B) is preferably 1 m 2 / g~100m 2 / g, more preferably 2m 2 / g~80m 2 / g, more preferably 5m 2 / g~50m 2It should be noted that, in this specification, the BET specific surface area of calcium carbonate constituting the surface-treated calcium carbonate (B) is a value measured using a specific surface area measuring device (Macsorb HM model-1208 manufactured by Mountech or FlowSorb II2300 manufactured by Micromeritics).
[0074] The BET specific surface area of calcium carbonate forming the surface-treated calcium carbonate (B) is 1 m 2 When the BET specific surface area of calcium carbonate forming the surface-treated calcium carbonate (B) is 100 m 2 / g or less, in the resin composition, the aggregation of the surface-treated calcium carbonate (B) is restricted, the dispersibility of the surface-treated calcium carbonate (B) in the resin composition becomes good, and as a result, the resin composition has good thixotropy.
[0075] The content of the surface-treated calcium carbonate (B) in the resin composition is preferably 10 to 400 parts by weight, more preferably 30 to 300 parts by weight, further preferably 50 to 200 parts by weight, more preferably 75 to 175 parts by weight, and particularly preferably 80 to 150 parts by weight, relative to 100 parts by weight of the polyoxyalkylene polymer (A).
[0076] The fatty acid compound related to the surface-treated calcium carbonate (B) in the present resin composition can be considered as a surface treatment agent for calcium carbonate. The fatty acid compound is not particularly limited, and can be appropriately cited as one or more selected from fatty acids, salts of fatty acids, derivatives of fatty acids, and salts of derivatives of fatty acids.
[0077] The fatty acid is not particularly limited, and saturated fatty acids, unsaturated fatty acids, alicyclic carboxylic acids, and the like can be preferably used. Specific examples include caproic acid, caprylic acid, nonanoic acid, capric acid, undecanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, azelaic acid, behenic acid, lignoceric acid, hexadecanoic acid, montanic acid, melissic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, obtusilic acid, caproleic acid, undecenoic acid, dodec-5-enoic acid, tsuzuic acid, physeteric acid, myristoleic acid, palmitoleic acid, petroselinic acid, oleic acid, elaidic acid, asclepinic acid, vaccenic acid, gadoleic acid, gondoic acid, cetoleic acid, erucic acid, brassidic acid, selacholeic acid Acid, simmondsia chinensis, lumichenic acid, sorbic acid, linoleic acid, stearyl stearate, lauryl stearate, stearyl palmitate, lauryl palmitate, etc. These compounds can be used alone or in combination of two or more. Among the above-mentioned fatty acids, palmitic acid, stearic acid, and oleic acid are particularly preferred.
[0078] For fatty acid compounds, in 100 mol %, the carbon number of hydrocarbon components is 14 or less fatty acid compounds 12 mol %, preferably 11.0 mol %, more preferably 10.0 mol %, further preferably 9.0 mol %, more preferably 8.0 mol %, more preferably 7.0 mol %, more preferably 6.0 mol %, more preferably 5.0 mol %, more preferably 4.0 mol %, more preferably 3.0 mol %, preferably 2.0 mol %, more preferably 1.0 mol %, particularly preferably 0.5 mol %, most preferably substantially not. In 100 mol %, the carbon number of hydrocarbon components is 14 or less fatty acid compounds can be 0 mol %. For fatty acid compounds, when the amount of fatty acid compounds containing hydrocarbon components with carbon atoms of less than 14 is less than 12.0 mol % in 100 mol % of the fatty acid compounds, the cohesive force of the surface-treated calcium carbonate (B) in the resin composition is reduced, and the viscosity increase of the resin composition is reduced, thereby improving the storage stability of the resin composition.
[0079] In the case of surface treatment of calcium carbonate using "100 mol % of fatty acid compounds including 12 mol % or less of fatty acid compounds with carbon atoms of 14 or less in hydrocarbon components" as a surface treatment agent, the obtained calcium carbonate (i.e., surface-treated calcium carbonate) may contain "100 mol % of fatty acid compounds including 12 mol % or less of fatty acid compounds with carbon atoms of 14 or less in hydrocarbon components" on the surface. Therefore, one embodiment of the present invention can be described as follows:
[0080] A resin composition for a pre-packaged curable resin composition, comprising:
[0081] 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group,
[0082] 10 to 400 parts by weight of calcium carbonate (B) containing a fatty acid compound and 2 to 70 parts by weight of an epoxy compound (C) are contained on the surface of the calcium carbonate.
[0083] In 100 mol % of the fatty acid compounds, the fatty acid compounds contain 12 mol % or less of fatty acid compounds having a hydrocarbon component with 14 or less carbon atoms.
[0084] The amount of fatty acid compounds used to surface-treat calcium carbonate (also referred to as the treatment amount using fatty acid compounds) is preferably 0.1 to 40.0 parts by weight relative to 100 parts by weight of calcium carbonate, preferably 0.3 to 30.0 parts by weight, more preferably 0.5 to 20.0 parts by weight, more effectively 0.7 to 15.0 parts by weight, and further preferably 1.0 to 10.0 parts by weight. When the treatment amount of fatty acid relative to calcium carbonate is more than 0.1 parts by weight, the entire surface of the calcium carbonate particles is surface-treated, and the effect of surface-treated calcium carbonate can be fully exerted, so it is preferred. In addition, when the treatment amount of fatty acid is less than 40.0 parts by weight, an effect proportional to the surface treatment amount can be obtained, and relative to cost, the effect of surface treatment is sufficient, so it is preferred.
[0085] The amount of fatty acid compounds attached to the surface of the surface-treated calcium carbonate (i.e., surface-treated calcium carbonate (B)) (also referred to as the surface attachment amount of fatty acid compounds) is preferably the same as or substantially the same as the amount of fatty acid compounds used for the surface treatment. That is, the surface attachment amount of fatty acid compounds in the surface-treated calcium carbonate (B) is preferably 0.1% to 40.0% by weight, preferably 0.3% to 30.0% by weight, more preferably 0.5% to 20.0% by weight, more preferably 0.7% to 15.0% by weight, and further preferably 1.0% to 10.0% by weight, in 100% by weight of the surface-treated calcium carbonate (B). With respect to the surface attachment amount of fatty acid compounds in the surface-treated calcium carbonate (B), when (a) is 0.1% by weight or more in 100% by weight of the surface-treated calcium carbonate (B), the effect as the surface-treated calcium carbonate can be fully exerted, and therefore it is preferred, and when (b) is 40.0% by weight or less, an effect proportional to the surface treatment amount can be obtained, and therefore it is preferred.
[0086] The amount of fatty acid compounds attached to the surface of the surface-treated calcium carbonate (B) can be measured, for example, using differential thermal analysis (TGD9600 manufactured by ULVAC) according to the following operations (1) to (4): (1) Calcium carbonates A to G (surface-treated calcium carbonates) are heated so that the temperature of the surface-treated calcium carbonates is increased from room temperature to 500°C at a rate of 10°C / min; (2) The weight of the surface-treated calcium carbonate when the surface-treated calcium carbonate is 200°C and the weight of the surface-treated calcium carbonate when the surface-treated calcium carbonate is 500°C are respectively measured; (3) The heating loss (%) is calculated by the following formula, and the obtained heating loss (%) is used as the amount (%) of fatty acid compounds attached to 100% by weight of the surface-treated calcium carbonate.
[0087] Heating weight loss (%) = [(weight of surface-treated calcium carbonate at 200°C (g) - weight of surface-treated calcium carbonate at 500°C (g)) / weight of surface-treated calcium carbonate at 200°C (g)] × 100
[0088] (4) Based on the obtained heating loss, the amount of the fatty acid compound in 100 parts by weight of the surface-treated calcium carbonate was calculated by the following formula.
[0089] The amount of the fatty acid compound in the surface-treated calcium carbonate (parts by weight) = [weight loss on heating (%) × amount of the surface-treated calcium carbonate (parts by weight) / 100].
[0090] The method for producing the surface-treated calcium carbonate (B) is not particularly limited, and may include: using the above-mentioned fatty acid compound to surface-treat (coat) the above-mentioned calcium carbonate, and then, according to a common method, powdering through processes such as dehydration, drying, and pulverization. As the method for producing the surface-treated calcium carbonate (B), a fatty acid compound containing 12 mol% or less of fatty acid compounds having a carbon number of 14 or less in a hydrocarbon component in 100 mol% is used as a surface treatment agent, and other than this, there is no particular limitation, and the surface treatment method may be any method of a wet method or a dry method.
[0091] [Epoxy compounds (C)]
[0092] The epoxy compound (C) can function as a plasticizer in the resin composition. When the resin composition contains the epoxy compound (C), there is an advantage that the durability of the cured product formed from the resin composition is improved.
[0093] As epoxy compounds (C), as long as there are more than one epoxy group in the molecule, there is no particular limitation. As epoxy compounds (C), examples include: epoxidized unsaturated oils and fats, epoxidized unsaturated fatty acid esters, alicyclic epoxy compounds, compounds shown in epichlorohydrin derivatives, and mixtures thereof. As epoxy compounds (C), specifically, epoxidized soybean oil, epoxidized linseed oil, 4,5-epoxycyclohexane-1,2-dicarboxylic acid bis (2-ethylhexyl) ester (E-PS), octyl epoxy stearate, and butyl epoxy stearate, 3,4-epoxycyclohexanecarboxylic acid 3',4'-epoxycyclohexyl methyl ester (celloxide 2021P), etc., preferably 4,5-epoxycyclohexane-1,2-dicarboxylic acid bis (2-ethylhexyl) ester. These compounds can be used alone or in combination of two or more.
[0094] Relative to 100 parts by weight of the polyoxyalkylene polymer (A), the content of the epoxy compound (C) in the resin composition is preferably 1 part by weight to 120 parts by weight, preferably 2 parts by weight to 100 parts by weight, more preferably 2 parts by weight to 80 parts by weight, further preferably 3 parts by weight to 70 parts by weight, and particularly preferably 5 parts by weight to 55 parts by weight.
[0095] [Photocurable substance (D)]
[0096] The present resin composition preferably further contains a photocurable substance (D). In the case where the present resin composition further contains a photocurable substance (D), by forming a film of the photocurable substance on the surface of the cured product formed by the resin composition, there is an advantage that the stickiness and weather resistance of the cured product can be improved. A photocurable substance refers to a substance whose molecular structure undergoes chemical changes in a very short period of time under the action of light, resulting in changes in physical properties such as curing.
[0097] As the photocurable material (D), many materials including organic monomers, oligomers, resins, or compositions containing these are known, and any commercially available material can be used. Representative materials include unsaturated acrylic compounds, polyvinyl cinnamate, and azidized resins.
[0098] Examples of unsaturated acrylic compounds include monomers, oligomers, or mixtures thereof having one or more acrylic or methacrylic unsaturated groups, such as propylene (or butylene, ethylene) glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, or oligoesters having a molecular weight of 10,000 or less. Specific examples include special acrylates (difunctional) such as ARONIX M-210, ARONIX M-215, ARONIX M-220, ARONIX M-233, ARONIX M-240, and ARONIX M-245; (trifunctional) such as ARONIX M-305, ARONIX M-309, ARONIX M-310, ARONIX M-315, ARONIX M-320, and ARONIX M-325; and (multifunctional) such as ARONIX M-400. Particularly preferred are compounds containing an acrylic functional group, and preferred are compounds containing an average of three or more identical functional groups in one molecule. (All of the above ARONIX are products of Toagosei Co., Ltd.).
[0099] Polyvinyl cinnamate is a photosensitive resin having a cinnamoyl group as a photosensitive group, and includes a variety of polyvinyl cinnamate derivatives in addition to those obtained by esterifying polyvinyl alcohol with cinnamic acid to diol.
[0100] Azide resins are known to be photosensitive resins with an azide group as a photosensitive group. In general, in addition to rubber photosensitive liquids that add diazide compounds as photosensitizers, detailed examples are also given in "Photosensitive Resins" (published on March 17, 1977, issued by the Printing Society Publishing Department, pages 93, 106, and 117). They can be used alone or in combination, and a sensitizer can be added as needed. It should be noted that the effect is sometimes improved when a sensitizer such as ketones and nitro compounds or an accelerator such as amines is added.
[0101] The content of the photocurable substance (D) in the resin composition is preferably 0.5 to 20.0 parts by weight, and more preferably 0.1 to 10.0 parts by weight, relative to 100 parts by weight of the polyoxyalkylene polymer (A). When the content of the photocurable substance (D) in the resin composition is within the above range, the resin composition can provide a pre-packaged curable resin composition, which can provide a cured product that is excellent in weather resistance, soft, and not prone to cracking.
[0102] [Hollow filler (E)]
[0103] The present resin composition preferably further contains a hollow filler (E). The hollow filler is a spherical filler that is hollow inside. When the present resin composition contains a hollow filler, the resin composition and a cured product formed from the resin composition can be made lighter.
[0104] Examples of the hollow filler (E) include organic hollow spheres and inorganic hollow spheres. Examples of the material of the hollow filler (E) include inorganic materials such as glass, white sand, and silica, and organic materials such as phenolic resin, urea resin, polystyrene, and saran. The hollow filler (E) is particularly preferably a hollow glass sphere made of glass.
[0105] The content of the hollow filler (E) in the resin composition is preferably 0.01 to 100.00 parts by weight, more preferably 0.10 to 30.00 parts by weight, particularly preferably 0.20 to 20.00 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0106] The volume average particle size of the hollow filler (E) is preferably 5 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 20 μm to 150 μm. The volume average particle size of the hollow filler (E) can be measured using a laser diffraction particle size distribution analyzer.
[0107] Usually, based on the volume concentration in 100.0vol% of the compounding type curable resin composition, it is preferred to add 0.2vol% to 5.0vol% of the hollow filler (E), and more preferably 0.3vol% to 3.0vol%. When the volume concentration of the hollow filler (E) in 100.0vol% of the compounding type curable resin composition is 0.2vol% or more, there is an advantage of no roughness. When the volume concentration of the hollow filler (E) in 100.0vol% of the compounding type curable resin composition is 5.0vol% or less, (a) since the viscosity of the compounding type curable resin composition will not become too high, it has the advantage of good operability, and (b) since the modulus of the obtained cured product will not become too high, there is an advantage that there is no tendency for the basic performance of the compounding type curable resin composition to be impaired. It should be noted that "vol%" means "volume %".
[0108] [Phthalate ester compound (F)]
[0109] The present resin composition may further include a phthalate compound (F). The phthalate compound (F) is an ester with phthalic acid as the main skeleton. The phthalate compound (F) can function as a plasticizer in the resin composition. When the present resin composition further includes a phthalate compound (F), the resin composition has the advantage of being able to provide a pre-packaged curable resin composition, and the pre-packaged curable resin composition can provide a cured product with excellent adhesion.
[0110] The phthalate compound (F) is not particularly limited, and examples thereof include dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, di-n-hexyl phthalate, bis(2-ethylhexyl) phthalate, di-n-octyl phthalate, diisononyl phthalate, dinonyl phthalate, diisodecyl phthalate, diisoundecyl phthalate, dibutylbenzyl phthalate, and the like. Preferred examples include dibutyl phthalate, diisononyl phthalate (DINP), diheptyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate (DIDP), and butylbenzyl phthalate.
[0111] Relative to 100 parts by weight of the polyoxyalkylene polymer (A), the content of the phthalate compound (F) in the resin composition is preferably 0 to 200 parts by weight, preferably 30 to 170 parts by weight, more preferably 50 to 150 parts by weight, more preferably 70 to 130 parts by weight, and particularly preferably 90 to 110 parts by weight, calculated as the total amount with the epoxy compound (C).
[0112] [Other ingredients]
[0113] The present resin composition may further include heavy calcium carbonate without surface treatment. When the resin composition further includes heavy calcium carbonate without surface treatment, the resin composition and the pre-packaged curable resin composition containing the resin composition have the advantages of (a) reducing the viscosity increase, and (b) providing a cured product with excellent strength.
[0114] From the viewpoint of improving the thixotropy of the resin composition, the BET specific surface area of the heavy calcium carbonate without surface treatment is preferably 0.1 m 2 / g~10.0m 2 / g, more preferably 0.2m 2 / g~8.0m 2 / g, more preferably 0.5m 2 / g~5.0m 2 It should be noted that, in this specification, the BET specific surface area of heavy calcium carbonate without surface treatment is a value measured using a specific surface area measuring device (Macsorb HM model-1208 manufactured by Mountech or FlowSorb II2300 manufactured by Micromeritics).
[0115] Relative to 100 parts by weight of the polyoxyalkylene polymer (A), the content of the unsurface-treated heavy calcium carbonate in the present resin composition is preferably 3 parts by weight to 200 parts by weight, preferably 5 parts by weight to 170 parts by weight, more preferably 10 parts by weight to 150 parts by weight, more preferably 20 parts by weight to 120 parts by weight, and particularly preferably 30 parts by weight to 100 parts by weight.
[0116] The present resin composition may further include a light stabilizer. When the resin composition further includes a light stabilizer, the resin composition has the advantage of being able to provide a pre-packaged curable resin composition capable of providing a cured product with reduced oxidation and degradation caused by light.
[0117] Examples of the light stabilizer include benzotriazole compounds, hindered amine compounds, benzoate compounds, etc. As the light stabilizer, hindered amine compounds are particularly preferred.
[0118] The content of the light stabilizer in the resin composition is preferably 0.1 to 10.0 parts by weight, more preferably 0.2 to 5.0 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0119] The present resin composition may further include an ultraviolet absorber. In the case where the resin composition further includes an ultraviolet absorber, the resin composition has the advantage of being able to provide a pre-packaged curable resin composition capable of providing a cured product having excellent surface weather resistance.
[0120] Examples of the ultraviolet absorber include benzophenone compounds, benzotriazole compounds, salicylate compounds, substituted tolyl compounds, and metal chelate compounds. Benzotriazole compounds are particularly preferred as the ultraviolet absorber.
[0121] The content of the ultraviolet absorber in the resin composition is preferably 0.1 to 10.0 parts by weight, more preferably 0.2 to 5.0 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0122] The present resin composition may further contain a thixotropy imparting agent (anti-dripping agent) in order to prevent dripping and improve workability.
[0123] The thixotropy-imparting agent is not particularly limited, and examples thereof include polyamide waxes, hydrogenated castor oil derivatives, metal soaps such as calcium stearate, aluminum stearate, and barium stearate, etc. These compounds may be used alone or in combination of two or more.
[0124] The content of the thixotropy-imparting agent in the present resin composition is not particularly limited, but is preferably 0.1 to 20.0 parts by weight relative to 100 parts by weight of the polyoxyalkylene polymer (A).
[0125] The present resin composition may contain a plasticizer other than the epoxy compound (C) and the phthalate compound (F).
[0126] The plasticizer other than the epoxy compound (C) and the phthalate compound (F) is not particularly limited, and examples thereof include: non-phthalate compounds such as diisononyl 1,2-cyclohexanedicarboxylate; aliphatic polycarboxylic acid ester compounds such as dioctyl adipate, dioctyl sebacate, dibutyl sebacate, diisodecyl succinate, and acetyl tributyl citrate; unsaturated fatty acid ester compounds such as butyl oleate and methyl acetyricinoleate; alkyl phenyl sulfonate; phosphate compounds; trimellitate compounds; chlorinated paraffin; hydrocarbon oils such as alkyl diphenyl and partially hydrogenated terphenyl; process oil, etc. These compounds may be used alone or in combination of two or more.
[0127] As plasticizers other than epoxy compounds (C) and phthalate compounds (F), (a) acrylic compounds, (b) polyoxyalkylene polymers having 0.3 to 1.2 reactive silicon groups in one molecule, (c) acrylic polymers having 0.3 to 1.2 reactive silicon groups in one molecule, etc. can be used. These compounds have the effect of improving the stain resistance of the cured product provided by the formulation-type curing resin composition containing the resin composition. In addition, (a) acrylic compounds and (c) acrylic polymers having 0.3 to 1.2 reactive silicon groups in one molecule have the effect of improving the weather resistance of the above-mentioned cured product. These compounds can be used alone or in combination of two or more.
[0128] Relative to 100 parts by weight of the polyoxyalkylene polymer (A), the content of plasticizers other than the epoxy compound (C) and the phthalate compound (F) in the present resin composition is preferably 0 to 200 parts by weight, preferably 30 to 170 parts by weight, more preferably 50 to 150 parts by weight, more preferably 70 to 130 parts by weight, and particularly preferably 90 to 110 parts by weight, calculated on the total amount of the epoxy compound (C) and the phthalate compound (F).
[0129] The amount of water (moisture content) in the resin composition is not particularly limited, but is preferably 200 ppm to 10,000 ppm, more preferably 500 ppm to 8,000 ppm, further preferably 1,000 ppm to 7,000 ppm, and particularly preferably 1,500 ppm to 6,000 ppm based on 100 parts by weight of the resin composition from the viewpoint of achieving better storage stability.
[0130] The present resin composition may further contain a tackifier. When the resin composition further contains a tackifier, the resin composition has advantages that the adhesiveness to the substrate is improved and the strength is also increased.
[0131] Examples of the thickener include aminosilane compounds, epoxysilane compounds, isocyanatesilane compounds, acrylic silane compounds, etc. As the thickener, aminosilane compounds are particularly preferred.
[0132] The content of the tackifier in the present resin composition is preferably 0.1 to 10.0 parts by weight, more preferably 0.2 to 5.0 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0133] The present resin composition may further contain a solvent and / or a diluent. When the resin composition further contains a solvent and / or a diluent, the resin composition has an advantage of reduced viscosity and improved handleability.
[0134] Examples of the solvent and diluent include low-viscosity liquid compounds such as hydrocarbon compounds, aromatic compounds, alcohols, esters, and silicone oils.
[0135] The content of the solvent and / or diluent in the present resin composition is preferably 0.1 to 20.0 parts by weight, more preferably 0.2 to 10.0 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0136] The present resin composition may further contain an antioxidant. When the resin composition further contains an antioxidant, the resin composition has the advantages of being able to delay deterioration even when stored for a long period of time and being able to maintain performance even when stored under high temperature conditions.
[0137] Examples of the antioxidant include hindered phenol compounds, monophenol compounds, polyphenol compounds, etc. As the antioxidant, hindered phenol compounds are particularly preferred.
[0138] The content of the antioxidant in the resin composition is preferably 0.1 to 10.0 parts by weight, more preferably 0.2 to 5.0 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0139] In addition to the polyoxyalkylene polymer (A), the present resin composition may also contain an acrylic polymer having a reactive silicon group, a saturated hydrocarbon polymer having a reactive silicon group, etc. The acrylic polymer having a reactive silicon group and the saturated hydrocarbon polymer having a reactive silicon group can significantly improve the heat resistance and / or weather resistance of the cured product provided by the pre-packaged curable resin composition containing the resin composition. Therefore, when the resin composition is used as a building sealing material and / or an industrial sealing material, it has the advantage of significantly extending the sealing life.
[0140] The amount of these used is preferably 10 to 300 parts by weight, more preferably 20 to 200 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0141] The present resin composition may contain a flame retardant, a curing property adjuster, a lubricant, a pigment, a foaming agent, a mildewproofing agent, and the like in addition to the above.
[0142] [Method for producing a resin composition for a pre-packaged curable resin composition]
[0143] The method for manufacturing a resin composition for a pre-packaged curable resin composition according to one embodiment of the present invention comprises the step of mixing 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group, 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and 2 to 70 parts by weight of an epoxy compound (C), wherein, out of 100 mol % of the fatty acid compound, the fatty acid compound contains less than 12 mol % of fatty acid compounds having a hydrocarbon component with a carbon number of less than 14.
[0144] In this specification, hereinafter, "a method for producing a resin composition for a packaged curable resin composition according to one embodiment of the present invention" may be referred to as "this production method".
[0145] Since the present production method has the above-mentioned configuration, it has an advantage of being able to provide a pre-packaged curable resin composition having excellent storage stability even in a high-temperature and high-humidity environment.
[0146] Hereinafter, each embodiment of the present production method will be described, and in addition to the matters described in detail below, the description of the item [resin composition for batch-packaged curable resin composition] will be appropriately cited.
[0147] In the step (mixing step) of mixing the polyoxyalkylene polymer (A), calcium carbonate (B) and epoxy compound (C) in the present production method, there is no particular limitation on the method (mixing method) for mixing these components. As the mixing method, for example, (1) a method of mixing the above-mentioned components using a mixer, a roller, a kneader, etc. at room temperature (e.g., 15°C to 30°C) or under heating (e.g., 50°C to 120°C); or (2) a method of dissolving the components in a small amount using an appropriate solvent and mixing the dissolved components, etc., can be used.
[0148] Reducing the amount of water in the resin composition results in obtaining a resin composition having excellent storage stability. From this point of view, the present production method preferably further comprises a step of dehydrating and / or drying the resin composition obtained in the mixing step.
[0149] As a method for dehydrating and / or drying the resin composition, (a) when the resin composition is a solid such as a powder, a heating drying method or a reduced pressure dehydration method is preferably used, and (b) when the resin composition is a liquid, a reduced pressure dehydration method or a dehydration method using synthetic zeolite, activated alumina, silica gel, quicklime, magnesium oxide, etc. is preferably used. In addition to the above method, alkoxysilane compounds such as n-propyltrimethoxysilane, vinyltrimethoxysilane, vinylmethyldimethoxysilane, methyl silicate, ethyl silicate, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane, and γ-glycidoxypropyltrimethoxysilane can also be added to the resin composition to react with the water (water content) in the resin composition to dehydrate. In addition, 3-ethyl-2-methyl-2-(3-methylbutyl)-1,3- Oxazolidine, etc. The oxazolidine compound is added to the resin composition and reacts with water (moisture) in the resin composition to dehydrate. Alternatively, an isocyanate compound can be added to a small amount of the resin composition to react with the isocyanate group with water (moisture) in the resin composition to dehydrate.
[0150] [Prepared curable resin composition]
[0151] The packaged curable resin composition according to one embodiment of the present invention includes the resin composition described in [Resin composition for packaged curable resin composition] or a resin composition obtained by the production method described in [Method for producing resin composition for packaged curable resin composition].
[0152] In one embodiment of the present invention, since the resin composition for the compounding type curing resin composition and the curing agent are stored separately before being prepared into the compounding type curing resin composition, the resin composition for the compounding type curing resin composition can be stored for a longer period of time and more stably compared to the one-component curing resin composition. In other words, the present resin composition and / or the resin composition obtained by the present manufacturing method can be prepared into a compounding type curing resin composition by mixing with a curing agent just before construction.
[0153] The packaged curable resin composition according to one embodiment of the present invention may further contain a curing agent.
[0154] [Curing agent]
[0155] The curing agent is a mixture containing ingredients such as a curing catalyst, a filler, a plasticizer and water.
[0156] Examples of the curing catalyst include known curing catalysts such as dibutyltin diacetylacetonate, stannous octoate, dibutyltin dioctoate, dibutyltin dilaurate, dibutyltin maleate, dibutyltin diacetate, dibutyltin oxide, dibutyltin bistriethoxysilicate, dibutyltin distearate, dioctyltin dilaurate, dioctyldineodecanoyloxide, tin octoate, versatic acid, and tin naphthenate.
[0157] As a curing catalyst for the packaged curable resin composition in one embodiment of the present invention, tin octylate can be preferably used because it is excellent in the curing speed and / or durability of the cured product.
[0158] In order to improve the activity of the curing catalyst, an amine compound may be used in combination as a curing catalyst. Examples of such amine compounds include well-known amine compounds such as octylamine, decylamine, laurylamine, oleylamine, and di-n-octylamine.
[0159] The filler and plasticizer contained in the curing agent are not particularly limited, and may be known substances.
[0160] The curing agent can be produced by conventional methods, for example, (1) a method in which components such as a curing catalyst, a filler, a plasticizer and water are mixed at room temperature or under heating using a mixer, a roller or a kneader; or (2) a method in which a small amount of an appropriate solvent is used to dissolve the above-mentioned components and the dissolved products of the components are mixed.
[0161] [Masterbatch]
[0162] The pre-packaged curable resin composition according to one embodiment of the present invention may further include a masterbatch. By including a masterbatch in the pre-packaged curable resin composition, the color of the resulting cured product can be adjusted as desired.
[0163] The masterbatch may be a commercially available masterbatch. Specifically, the masterbatch may include a paste-like mixture containing pigments such as tin oxide, carbon black, titanium oxide, and red iron, a filler such as calcium carbonate and kaolin, and a plasticizer, without particular limitation.
[0164] The pigment, filler and plasticizer contained in the masterbatch are not particularly limited and may be known substances. In addition, the pigment, filler and plasticizer may be used alone or in combination of two or more.
[0165] The amount of the masterbatch used is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, based on 100 parts by weight of the polyoxyalkylene polymer (A).
[0166] [cured material]
[0167] A cured product can be obtained by curing the pre-packaged curable resin composition according to one embodiment of the present invention. A cured product obtained by curing the pre-packaged curable resin composition according to one embodiment of the present invention is also one embodiment of the present invention.
[0168] The method for preparing a cured product according to one embodiment of the present invention is not particularly limited. Specifically, for example, a cured product can be obtained by sequentially performing the following operations (1) and (2): (1) using a mold frame, for example, made of polyethylene, to mold the formulation-type curing resin composition into a sheet with a thickness of 3 mm in a manner that does not introduce air bubbles, thereby preparing a sheet sample; (2) placing the sheet sample prepared in (1) at 23°C and 50% RH (relative humidity) for 3 days, and then further placing it at 50°C and 50% RH for 4 days, thereby obtaining a sheet-like cured product.
[0169] Since the cured product according to one embodiment of the present invention has the above-mentioned structure, it has the advantage of being excellent in tensile properties such as 100% stress (modulus), strength at break (breaking strength), and elongation at break (breaking elongation).
[0170] Example
[0171] Hereinafter, one embodiment of the present invention will be described in more detail by way of examples. However, the present invention is not limited to the following examples.
[0172] <Materials>
[0173] The materials used in the examples and comparative examples are as follows.
[0174] [Polyoxyalkylene polymer (A)]
[0175] As the polyoxyalkylene polymer (A), KANEKA MSPOLYMERS 810 manufactured by Kaneka Corporation was used.
[0176] KANEKA MS POLYMERS 810 is a polyoxyalkylene polymer having about two methyldimethoxysilyl groups as reactive silicon groups per molecule and having a polyoxypropylene unit in the main chain skeleton. The number average molecular weight (Mn) of KANEKA MS POLYMERS 810 is 26,000.
[0177] [Surface treated calcium carbonate (B)]
[0178] Colloidal calcium carbonate is treated with a fatty acid compound, wherein the fatty acid compound is a mixture of a plurality of fatty acids and is used as calcium carbonate A to G. Calcium carbonates A to G are surface-treated calcium carbonates. (a) The composition of each fatty acid contained in 100 mol% of the fatty acid compound of calcium carbonate A to G, (b) The BET specific surface area (m 2 / g), and (c) the adhesion amount of the fatty acid compound are shown in Table 1. In addition, the colloidal calcium carbonate was not subjected to surface treatment and was used as calcium carbonate H. The BET specific surface area (m 2 / g) are shown in Table 1.
[0179]
[0180] In Table 1, C represents the number of carbon atoms of each fatty acid, and when the fatty acid has an unsaturated bond, the number of the unsaturated bond is also described.
[0181] The amount of fatty acid compound attached to each of calcium carbonates A to G was measured using a differential thermal analyzer (TGD9600 manufactured by ULVAC Co., Ltd.) in accordance with the following operations (1) to (3): (1) calcium carbonates A to G (surface-treated calcium carbonates) were heated from room temperature to 500° C. at a rate of 10° C. / min; (2) the weight of the surface-treated calcium carbonate when the surface-treated calcium carbonate was 200° C. and the weight of the surface-treated calcium carbonate when the surface-treated calcium carbonate was 500° C. were measured respectively; (3) the heating loss (%) was calculated by the following formula, and the obtained heating loss (%) was used as the surface attachment amount (weight %) of the fatty acid compound in 100 weight % of the surface-treated calcium carbonate.
[0182] Heating weight loss (%) = [(weight of surface-treated calcium carbonate at 200°C (g) - weight of surface-treated calcium carbonate at 500°C (g)) / weight of surface-treated calcium carbonate at 200°C (g)] × 100
[0183] [Heavy calcium carbonate]
[0184] As the heavy calcium carbonate, LM2200 manufactured by Dongguan Limao Chemical Co., Ltd. was used. This heavy calcium carbonate was not surface treated and had a BET specific surface area of 1.1 m 2 / g.
[0185] [Epoxy compounds (C)]
[0186] As the epoxy compound, SANSO CIZER E-PS manufactured by Shin Nippon Rika Co., Ltd. or JDH22E manufactured by Zhejiang Jiaao Enprotech Stock Co., Ltd. was used. Both are di(2-ethylhexyl)-4,5-epoxycyclohexane-1,2-dicarboxylate.
[0187] [Photocurable substance (D)]
[0188] As the photocurable material, ARONIX M309 manufactured by Toagosei Co., Ltd., which is trimethylolpropane triacrylate, was used.
[0189] [Hollow filler (E)]
[0190] As the hollow filler, H25 manufactured by SINOSTEEL MAANSHAN NEW MATERIAL TECHNOLOGY CO., LTD., which is a hollow glass filler having a volume average particle size of 95 μm, was used.
[0191] [Phthalates (F)]
[0192] As the phthalate (F), DIDP manufactured by J-PLUS or DINP manufactured by J-PLUS was used. DIDP is diisodecyl phthalate, and DINP is diisononyl phthalate.
[0193] [Ultraviolet light absorber]
[0194] As the ultraviolet absorber, Tinuvin 326 manufactured by BASF, which is a benzotriazole compound, was used.
[0195] [Light stabilizer]
[0196] As the light stabilizer, Tinuvin 770 manufactured by BASF Corporation, which is a hindered amine compound, was used.
[0197] [Thixotropy-imparting agent]
[0198] As the thixotropy-imparting agent, DISPARLON 308 manufactured by Kusumoto Chemicals Co., Ltd., which is a hydrogenated castor oil derivative, was used.
[0199] [Curing agent]
[0200] The following components were weighed: (a) 3.0 parts by weight of tin octanoate, a product name of NEOSTANN U-28 manufactured by Nitto Kasei Co., Ltd. as a curing catalyst; (b) 0.6 parts by weight of lauryl amine manufactured by Wako Pure Chemical Industries, Ltd.; (c) 6.4 parts by weight of diisodecyl phthalate manufactured by J-PLUS; (d) 5.0 parts by weight of kaolin, a product name of ASP170 manufactured by BASF; and (e) 15 parts by weight of LM2200, a heavy calcium carbonate. The weighed raw materials were dispersed for 5 minutes using a homogenizer, and the resulting mixture was used as a curing agent.
[0201] [Masterbatch]
[0202] The following components were weighed: (a) 5.0 parts by weight of titanium oxide, trade name TIPAQUE R-820 manufactured by Ishihara Sangyo Co., Ltd. as a white pigment; (b) 4.0 parts by weight of DIDP as a plasticizer; and (c) 0.1 parts by weight of carbon black manufactured by ASAHI CARBON Co., Ltd. as a black pigment. The weighed raw materials were supplied to three coating rollers and dispersed, and the obtained mixture was used as a masterbatch.
[0203] <Evaluation Method>
[0204] Hereinafter, each evaluation method in Examples and Comparative Examples will be described.
[0205] [Viscosity of the resin composition for the pre-packaged curable resin composition]
[0206] 《Initial viscosity》
[0207] After the resin composition for the batch-packed curable resin composition was prepared, the resin composition was left to stand in a thermostatic chamber adjusted to 23°C and 50%RH for 1 day. Then, for the resin composition at a temperature of 23°C, the viscosity was measured at 2 rpm using a BS type viscometer (manufactured by TOKIMEC, rotor No. 7) as the initial viscosity (Pa·s). The results are shown in Table 2 or 3.
[0208] [Thickness increase ratio after storage at 50℃85%RH]
[0209] The resin composition for the compounding type curable resin composition is placed under the conditions of 50°C and 85%RH (relative humidity). From the beginning of the placement, the resin composition is taken out every week, and the resin composition is placed in a constant temperature chamber adjusted to 23°C 50%RH (relative humidity) for 5 hours. Then, for the resin composition at a temperature of 23°C, the viscosity at 2rpm is measured using the same device as above, as the viscosity (Pa·s) after storage at 50°C and 85%RH. For the resin composition for the compounding type curable resin composition, the ratio (%) of the viscosity after storage at 50°C and 85%RH to the above-mentioned initial viscosity is calculated as the viscosity increase rate (%) after storage at 50°C and 85%RH. The results are shown in Table 2 or 3. It should be noted that the result of placing under the conditions of 50°C and 85%RH is that when the resin composition for the compounding type curable resin composition gels or solidifies and the viscosity cannot be measured, the situation is recorded in Table 2 or 3.
[0210] [Method for producing cured product]
[0211] The Awatori Rentaro rotary / revolution mixer manufactured by THINKY was used to mix 100 parts by weight of the resin composition, 10 parts by weight of the curing agent and 3 parts by weight of the masterbatch for each of the compounding-type curable resin compositions obtained in the embodiments and comparative examples, and a compounding-type curable resin composition was prepared. A polyethylene mold was used to mold the obtained compounding-type curable resin composition into a sheet with a thickness of 3 mm in a manner that did not enter bubbles, and a sheet test body was prepared. The above-mentioned sheet test body was placed at 23°C and 50%RH for 3 days, and then further placed at 50°C and 50%RH for 4 days. By the method described above, a cured product was prepared.
[0212] [Tensile properties of cured product]
[0213] The obtained cured product was punched into a dumbbell shape No. 3 to prepare a test piece. Using the test piece, a tensile test (tensile speed 200 mm / min) was performed at 23°C (50% RH) to measure 100% stress (modulus), strength at break (breaking strength) and elongation at break (breaking elongation). The results are shown in Table 2 or 3.
[0214] <Examples and Comparative Examples>
[0215] (Example 1)
[0216] 100 parts by weight of polyoxyalkylene polymer (A) (KANEKA MS POLYMERS 810), 115 parts by weight of surface treated calcium carbonate (B) (calcium carbonate A), 20 parts by weight of epoxy compound (C) (E-PS), 3.0 parts by weight of photocurable substance (D) (M309), 10.00 parts by weight of hollow filler (E) (H25), 80 parts by weight of phthalate compound (F) (DIDP), 50 parts by weight of heavy calcium carbonate (LM2200), 1.0 parts by weight of ultraviolet absorber (Tinuvin 326), 1.0 parts by weight of light stabilizer (Tinuvin 770), and 3.0 parts by weight of thixotropy imparting agent (DISPARLON 308) were weighed and mixed for 3 minutes using a metal spatula. The mixture was supplied to three coating rollers at room temperature (25° C.) and kneaded to produce a resin composition for a pre-packaged curable resin composition. The initial viscosity of the obtained resin composition, the viscosity increase ratio after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured.
[0217] (Example 2)
[0218] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate B, and a resin composition for a pre-packaged curable resin composition was manufactured by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0219] (Example 3)
[0220] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate C, and a resin composition for a pre-packaged curable resin composition was manufactured by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0221] (Example 4)
[0222] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate D, and a resin composition for a pre-packaged curable resin composition was manufactured by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0223] (Comparative Example 1)
[0224] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate E, and a resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0225] (Comparative Example 2)
[0226] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate F, and a resin composition for a pre-packaged curable resin composition was manufactured by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0227] (Comparative Example 3)
[0228] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate G, and a resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 1. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of a cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0229] (Reference Example 1)
[0230] A resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 1 except that the surface-treated calcium carbonate (B) was not used but the calcium carbonate H without surface treatment was used. Next, the initial viscosity of the obtained resin composition, the viscosity increase rate after storage at 50° C. and 85% RH, and the tensile properties of the cured product containing the resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 2.
[0231]
[0232] The following results can be known from the results shown in Table 2. The resin composition for the curable resin composition of the dispensing type of Examples 1 to 4 as one embodiment of the present invention does not gel even when stored at 50°C and 85% RH for 4 weeks. That is, the resin composition for the dispensing type curable resin composition of Examples 1 to 4 as one embodiment of the present invention can be considered to have good storage stability under a high temperature and high humidity environment. On the other hand, for the resin composition for the dispensing type curable resin composition of Comparative Examples 1 to 3 outside the scope of the present invention containing surface-treated calcium carbonate (B), the surface-treated calcium carbonate (B) is surface-treated with a fatty acid compound containing more than 12 mol% of a fatty acid with a carbon number (C) of 14 or less in 100 mol% of the fatty acid compound, and gelled within 4 weeks when stored under 50°C and 85% RH. That is, the resin composition for the dispensing type curable resin composition of Comparative Examples 1 to 3 outside the scope of the present invention can be considered to have poor storage stability under a high temperature and high humidity environment. It is also known that the resin composition for a batch-packaged curable resin composition of Reference Example 1, which does not contain surface-treated calcium carbonate but contains non-surface-treated calcium carbonate H, provides a cured product having a small elongation at break.
[0233] (Example 5)
[0234] 100 parts by weight of a polyoxyalkylene polymer (A) (KANEKA MS POLYMERS 810), 140 parts by weight of a surface-treated calcium carbonate (B) (calcium carbonate D), 30 parts by weight of an epoxy compound (C) (JDH22E), 4.5 parts by weight of a photocurable substance (D) (M309), 15.00 parts by weight of a hollow filler (E) (H25), 80 parts by weight of a phthalate compound (F) (DINP), 30 parts by weight of heavy calcium carbonate (trade name: LM2200), 1.0 part by weight of an ultraviolet absorber (Tinuvin 326), 1.0 part by weight of a light stabilizer (Tinuvin 770), and 3.0 parts by weight of a thixotropy-imparting agent (DISPARLON 308) were weighed, and the mixture was supplied to three coating rollers at room temperature (25° C.) and kneaded to produce a resin composition for a pre-packaged curable resin composition. The initial viscosity of the obtained resin composition and the viscosity increase ratio after storage at 50° C. and 85% RH were measured. Table 3 shows the measurement results.
[0235] (Example 6)
[0236] A resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 5, except that the amount of the epoxy compound (C) (JDH22E) was changed to 50 parts by weight and the amount of the phthalate compound (F) (DINP) was changed to 60 parts by weight. Next, the initial viscosity and the viscosity increase rate after storage at 50°C and 85%RH of the obtained resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 3.
[0237] (Comparative Example 4)
[0238] A resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 5 except that the epoxy compound (C) (JDH22E) was not used and the amount of the phthalate compound (F) (DINP) was changed to 110 parts by weight. Next, the initial viscosity and the viscosity increase rate after storage at 50°C and 85%RH of the obtained resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 3.
[0239] (Comparative Example 5)
[0240] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate G, and a resin composition for a pre-packaged curable resin composition was prepared by the same method as in Comparative Example 4. Next, the initial viscosity of the obtained resin composition and the viscosity increase rate after storage at 50°C and 85%RH were measured in the same manner as in Example 1. The measurement results are shown in Table 3.
[0241] (Comparative Example 6)
[0242] The surface treated calcium carbonate (B) was changed from calcium carbonate A to calcium carbonate G, and a resin composition for a pre-packaged curable resin composition was prepared by the same method as in Example 5. Next, the initial viscosity and the viscosity increase rate after storage at 50° C. and 85% RH of the obtained resin composition were measured in the same manner as in Example 1. The measurement results are shown in Table 3.
[0243]
[0244] The following results can be known from the results shown in Table 3. For the resin composition for the compounding and packaging type curable resin composition of Examples 5 to 6 as one embodiment of the present invention, when stored at 50°C and 85% RH for 2 weeks, the viscosity increase is also suppressed to the extent that the viscosity can be measured. That is, the resin composition for the compounding and packaging type curable resin composition of Examples 5 to 6 as one embodiment of the present invention can be considered to have good storage stability under a high temperature and high humidity environment. On the other hand, the resin composition for the compounding and packaging type curable resin composition of Comparative Examples 4 to 5 outside the scope of the present invention that does not contain the epoxy compound (C) increases in viscosity within 2 weeks when stored at 50°C and 85% RH. That is, the resin composition for the compounding and packaging type curable resin composition of Comparative Examples 4 to 5 outside the scope of the present invention can be considered to have poor storage stability under a high temperature and high humidity environment. In addition, for the resin composition for the batch-packed curable resin composition of Comparative Example 6 outside the scope of the present invention, which contains surface-treated calcium carbonate (B), the surface-treated calcium carbonate (B) is surface-treated with a fatty acid compound containing more than 12 mol% of (C) fatty acids with carbon atoms of 14 or less in 100 mol% of the fatty acid compound, when stored under the conditions of 50° C. and 85% RH, the viscosity increases within 2 weeks to the extent that the viscosity cannot be measured. That is, the resin composition for the batch-packed curable resin composition of Comparative Example 6 outside the scope of the present invention can be considered to have poor storage stability under a high-temperature and high-humidity environment.
[0245] Industrial Applicability
[0246] According to one embodiment of the present invention, a resin composition for a pre-packaged curable resin composition having good storage stability even in a high temperature and high humidity environment can be provided. Therefore, one embodiment of the present invention can be preferably used in the fields of sealing materials, adhesives, bonding agents, waterproof materials, film waterproof materials, molding agents, shockproof materials, shock absorbing materials, sound insulation materials, foaming materials, coatings, and spray materials for buildings / ships / cars / roads, etc.
Claims
1. A resin composition for a pre-packaged curable resin composition, comprising: 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group, 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and Epoxy compound (C) 2 to 70 parts by weight, In 100 mol% of the fatty acid compounds, the fatty acid compounds do not contain fatty acid compounds having a hydrocarbon component with 14 or less carbon atoms.
2. The resin composition for a pre-packaged curable resin composition according to claim 1, wherein The calcium carbonate (B) surface-treated with the fatty acid compound contains colloidal calcium carbonate surface-treated with the fatty acid compound.
3. The resin composition for the pre-packaged curable resin composition according to claim 1 or 2, wherein The surface adhesion amount of the fatty acid compound is 1.0 to 10 parts by weight relative to 100 parts by weight of the calcium carbonate (B).
4. A method for producing a resin composition for a pre-packaged curable resin composition, the method comprising the step of mixing the following components (A) to (C): 100 parts by weight of a polyoxyalkylene polymer (A) having a reactive silicon group, 10 to 400 parts by weight of calcium carbonate (B) surface-treated with a fatty acid compound, and Epoxy compound (C) 2 to 70 parts by weight, In 100 mol% of the fatty acid compounds, the fatty acid compounds do not contain fatty acid compounds having a hydrocarbon component with 14 or less carbon atoms.
5. The method for producing a resin composition for a pre-packaged curable resin composition according to claim 4, wherein: The surface adhesion amount of the fatty acid compound is 1.0 to 10 parts by weight relative to 100 parts by weight of the calcium carbonate (B).
Citation Information
Patent Citations
JP1971027250B1
Poly - 1, 2 - - - - glycol ether and [poripuropirene[poripuropirene][buchirene[buchirene]telecom polio for treatment
JP1984015336B2
Production of unsaturated group-terminated polyalkylene oxide
JP1986215623A
Moisture-curing resin composition
JP1991047825A
Production of polyalkylene oxide
JP1998273512A